Multi-omics analyses of tumor-associated immune-infiltrating cells with the novel immune checkpoint protein tyrosine phosphatase 1B (PTP1B) in extracellular matrix of brain-lower-grade-glioma (LGG) and uveal-melanoma (UVM) - Bai, Kun-Hao; Zhu, Ming-Jiao; Zhang, Yi-Yang; Li, Xue-Ping; Chen, Si-Liang; Wang, Da-Wei; Dai, Yu-Jun (Frontiers in Immunology, 2022)
Immune checkpoint inhibitors represented by PD-1 have greatly changed the way cancer is treated. In addition to PD-1, new immune checkpoints are constantly excavated to better treat cancer. Recently, protein tyrosine phosphatase 1B (PTP1B) was identified as a new immune checkpoint and played a critical role in the treatment of tumors by inhibiting the proliferation and cytotoxicity of T cells induced by tumor antigen. To explore the targeting role of PTP1B in precision tumor therapy, we deeply analyzed the expression and prognosis of PTP1B in all tumors. Survival analysis results indicated that PTP1B was highly expressed in most tumor tissues and indicated poor prognosis in acute-myeloid-leukemia (LAML), brain-lower-grade-glioma (LGG), kidney-renal clear-cell-carcinoma (KIRC) and uveal-melanoma (UVM). The methylation status of PTP1B in these four tumors exhibited hypomethylation and mutation landscape showed that PTP1B had its specific characteristics in genomic instability and heterogeneity. The homologous recombination deficiency (HRD) and loss of heterozygosity (LOH) were positive related to PTP1B expression in liver-hepatocellular-carcinoma (LIHC) and kidney-chromophobe (KICH), while the immunescore and immune infiltration displayed a significant positive correlation with PTP1B expression in LGG and UVM. Drug sensitivity tests showed that the PTP1B inhibitor MSI-1436 had a sensitivity effect suppressing tumor cell viability and suggested it enhanced the efficacy of PD-1 inhibitors in cancers.